Study of Sports Medicine and Rehabilitation - Nadeem Ahme (Innovative Research Thoughts, 2018)
The specialisation in physical medicine and rehabilitation (PM&R) is unique in its ability to address the diversity of issues arising from the musculoskeletal system with diagnostic and non-chirurgical treatment. This covers wounds and illnesses affecting the limb and spine muscles, bones, articulations and nerves. Athletes, from teenage athletes to weekend warriors and experienced pros, are evaluated, treated and taught by the Johns Hopkins Sports Rehabilitation Program. Our staff is qualified to assist you recover from an accident, to identify risk factors or to enhance your athletic performance, so your favourite activities can take place over the next several years.